Exploring the Ethics of Deepfake Technology in Media: Implications for Trust and Information Integrity (Journal of Informatics Education and Research, 2024)
The advent of deepfake technology has introduced unprecedented challenges and opportunities within the media landscape, raising significant ethical concerns regarding trust and information integrity. This paper delves into the complex implications of deepfake technology, which utilizes advanced artificial intelligence to create highly realistic but fabricated audio and visual content. We explore the potential of deepfakes to undermine public trust, spread misinformation, and manipulate social and political discourse. Through a comprehensive analysis of notable case studies, the paper highlights the multifaceted risks associated with deepfakes, including their impact on personal privacy, security, and democratic processes. Additionally, we examine the current legal and regulatory frameworks addressing deepfake proliferation and assess their effectiveness in mitigating associated harms. The discussion extends to potential technological and policy-based solutions aimed at detecting and countering deepfake content, emphasizing the importance of media literacy and ethical standards in preserving information authenticity. Ultimately, this study underscores the critical need for a collaborative approach involving technologists, policymakers, and society at large to navigate the ethical challenges posed by deepfake technology and safeguard the integrity of information in the digital age.